2022
DOI: 10.1515/ipp-2022-4199
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and characterization of Alfa fibers and their use to produce Alfa/wool woven fabrics for composite reinforcement

Abstract: Because of their appealing properties, such as biodegradability, high basic stiffness, low density, and low cost, natural fibers have begun to be used in a variety of applications. In comparison to synthetics, they are also reusable. The aim of this work is to develop new woven materials made of wool and Alfa fibers (Stipa-tenacissima). The extraction of Alfa fibers was achieved via alkaline treatment. The chemical composition, mechanical and physical properties of the extracted fibers were determined. Wovens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Figure 2 shows a schematic of the woven manufacturing process and the prints of the manufactured woven are illustrated in Figure 3. The extraction of cellulose from the alfa plant was done with soda , we have already published an article on the method of extraction of cellulose from the alfa plant, 7 then the manual carding of the cellulose was done, then the spinning of the fibers to obtain continuous threads and finally the weaving of the taffetas type was done manually for 4 different types.
Figure 1.Photographs of yarns.
Figure 2.Woven preparation.
Figure 3.Photographs of the manufactured woven.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 shows a schematic of the woven manufacturing process and the prints of the manufactured woven are illustrated in Figure 3. The extraction of cellulose from the alfa plant was done with soda , we have already published an article on the method of extraction of cellulose from the alfa plant, 7 then the manual carding of the cellulose was done, then the spinning of the fibers to obtain continuous threads and finally the weaving of the taffetas type was done manually for 4 different types.
Figure 1.Photographs of yarns.
Figure 2.Woven preparation.
Figure 3.Photographs of the manufactured woven.
…”
Section: Methodsmentioning
confidence: 99%
“…6 In our case, we performed the treatment with NaOH. 7 The properties of fibers are linked to the concentration and duration of alkaline treatments. 8,9 Benyahia et al 10 study the effect of surface chemical changes on the composite properties of fiber polyester alfa mat, the scanning electron microscopy observations have shown that alkali-treatment enhanced the adhesion at the fiber matrix interface.…”
Section: Introductionmentioning
confidence: 99%